Po mochlos – prolegomena do możliwych jeszcze rozważań o kondycji uniwersytetu - Chojnacki, Marek; Żardecka, Magdalena (Człowiek i Społeczeństwo, 2020)
The text tackles the problem of the condition of university, in a world blindly believing that the only possible worth measure is economic in nature and, in the name of this belief, setting in motion a ruthless bureaucratic machinery that throttles all kinds of creativity and nips in the bud all nonstandard actions and creations. The world apparently is “out of joint”, and things are taking an unexpected turn. University is one of the victims, but also one of active accomplices of this despicable situation. How to speak about the university to those who are exclusively in business of calculating balance of profits and losses? How to speak about it after deconstruction, when all great ideas have been already repeatedly and manifoldly dismounted and discredited? How to speak about it, when the university’s men and women have discredited themselves repeatedly as well, oscillating between libido sciendi and libido dominandi? Trying to solve this puzzle, we are following in the footsteps of Derrida, who in his texts about university makes appeal to Kant, and inspired by his invention, we set in motion two opposite traditions, represented by Lyotard, Bourdieu, Bauman and Readings on the one hand, and by Humboldt, Schleiermacher and Jaspers on the other. With Derrida, we make noises about the return of the ideas of truth, of the light of reason, of the autonomy of university. It is, however, a return of the specters of the past, in alignment with Derrida’s hauntology. Humanists are people of academia who see these specters, but at the same time are already specters themselves – even if they still show up here and there, they are almost insignificant. They are only allowed to contemplate their negligibility and to confess their habitual helplessness. University always had to defend itself, and it does defend itself today.